Immunization with a Nontoxic/Nonfibrillar Amyloid-β Homologous Peptide Reduces Alzheimer’s Disease-Associated Pathology in Transgenic Mice - Sigurdsson, Einar M. (American Society for Investigative Pathology, 2001)
Transgenic mice with brain amyloid-β (Aβ) plaques immunized with aggregated Aβ1-42 have reduced cerebral amyloid burden. However, the use of Aβ1-42 in humans may not be appropriate because it crosses the blood brain barrier, forms toxic fibrils, and can seed fibril formation. We report that immunization in transgenic APP mice (Tg2576) for 7 months with a soluble nonamyloidogenic, nontoxic Aβ homologous peptide reduced cortical and hippocampal brain amyloid burden by 89% (P = 0.0002) and 81% (P = 0.0001), respectively. Concurrently, brain levels of soluble Aβ1-42 were reduced by 57% (P = 0.0019). Ramified microglia expressing interleukin-1β associated with the Aβ plaques were absent in the immunized mice indicating reduced inflammation in these animals. These promising findings suggest that immunization with nonamyloidogenic Aβ derivatives represents a potentially safer therapeutic approach to reduce amyloid burden in Alzheimer’s disease, instead of using toxic Aβ fibrils.